RETRACTED: Public Spending, Green Finance, and Zero Carbon for Sustainable Development: A Case of Top 10 Emitting Countries - Han, Feng; Farooq, Muhammad Umar; Nadeem, Muhammad; Noor, Malaika (Frontiers in Environmental Science, 2022)
In general, the public expenditure on schooling, science, and research and development (R&D) is thought to have a positive effect on the development and sustainability of an economy, but such evidence is lacking in the developing and developed countries, especially in the top 10 CO2-emitting countries. This study investigates the impact of public spending and green finance on environmental sustainability, using the ordinary least square method and data envelopment analysis, which uses the panel data from selected countries from 2008 to 2018. Results reveal a fluctuating green economic growth index, which was due to the non-serious existence of government policies. More precisely, a 1% increase in gross domestic product (GDP) growth increases the carbon emissions by about 0.40%, whereas the rise in coal consumption decreases environmental efficiency by about 0.88%. We also concluded that 0.95% GDP growth and economic development significantly enhance environmental emissions, whereas 0.5% of renewable energy consumption decreases the negative impact of environmental pollution. Furthermore, a 1% growth in renewable energy consumption improved environmental efficiency by 0.58%. Furthermore, the analysis demonstrates that the public expenditure on human capital and renewable energy (R&D) leads to a productive green economy through labor, and technically advance developmental practices, with varying consequences in distinctive countries.